Contemporary Islamic finance architecture - Abdul Rahman, Zaharuddin (IBFIM, 2014)
The growth of Islamic finance has been at very healthy stages throughout the past 20 years. Innovations and creativity of the Islamic banker with the help of Shariah scholars, has brought Islamic finance to a new level in which almost entire features of products offered by the conventional banks are now can be seen on the shelves of Islamic banks. Although it seems that they have about the similar features and functions but the substance of the products, especially from the contracts perspectives, they are very much different. It is repeatedly heard a call for Islamic finance to be entirely different from their conventional counterparts and that is by introducing more equity financing as compared to debt financing product. It is also said that this is more inline with the objectives of the Islamic law (Maqāṣid al-Sharīʾah). While it may be considedered as true and fair argument but that is not neccesarily the only way to achieve the Maqāṣid al-Sharīʾah. This is because based on the Islamic principle, mankind is not to limited to only an instrument for achiving the objective of Shariah in muʾāmalāt matters but the means can varies according to time, circumstances and sme other factors. One cannot deny of the huge task faced by Islamic Finance players in which they are obligated to meet several requirement such as the Shariah compliant, customer’s appetite and the land law, all at the same time. Furthermore, awaits the bigger and gigantic conventional counterparts to compete at the level playing field. This surely is not a simple task for anybody and any institution. Nonetheless, Islamic finance has proves that they are still able to grow at a very tremendous percentage. Having said so, Islamic finance is still exposed to a high level of Shariah risk especially when it comes to the execution and implementation stages. Eventhough the energy and commandable efforts which have been put by the Shariah advisors and the Shariah team, it seems that implementation is still considered as one of the biggest nuisance as it relying on the frontliners knowlegde and understanding of the products. In reality, it can be said that Islamic finance is depending a lot on the human capabilitis and knowledge. No matter how good is the product and the installed system, lack of understanding in the execution will always ruin the day. They are several insteresting suggestions to make compulsory of the external Shariah-audit prior to offcial approval of any yearly report of an Islamic bank. This is to target a better products execution which is proven lacking in the current situation and implementation. Currently in Malaysia, there is only an in-house Shariah auditing taken place, the external Shariah auditing only carried out by the central banks’ officer but not as strict as the professional auditing firms. To date, there is no clear requirement for the Islamic banks to have an independent auditing firm to organize a full Shariah audit and issue a separate Shariah certificate prior to submitting the financial year report to the central bank. In the absence of such requirement, literatures of Islamic finance which include appropriate description on product’s concept, contracts, relevant laws and regulations are in a great need to be further supplied. Let it be written by many scholars and practitioners based on various backgrounds, knowledges and experiences, where some of which, contains criticism from opponents of Islamic banks while other may originate from the proponents. All these literatures are still neccesary to assist the increasing number of Islamic bankers, practitioners, students as well as scholars. It is hoped that the critics and healthy discussions on Islamic bank’s products will enrich the market and able to soar the Islamic finance industry to a better future.